(untitled) (TEST Ticontre. Theory Text Translation, 2020)
First Italian translation of the short story Paradise, work of the Russian writer Georgy Ivanovich Chulkov, first published in the literary magazine «Obrazovanie» in 1908. This short story is part of a limited corpus of texts which widely demonstrate the author’s tendency to autobiographism and the creation of literary prototypes. Intertextual references are also frequent. The translation is introduced by a critical essay in which is provided an overview of the different major ways of interpretation.